Erewhon like New Zealand like England like Utopia. Samuel Butler’s Refractions of National and Cultural Identities - Spinozzi, Paola (Cadernos de Literatura Comparada (teste), 2017)
While writing the history of European nations, nineteenth-century historiographers drew attention to foundation myths that valued national identities and encouraged people to preserve the nation’s unity. The creation of a utopian or dystopian place incorporates concepts of nation, nationality, and culture defining the native country of the writer. The construction of Great Britain as a nation in the Victorian age and portrayal of New Zealand as a colony of Queen Victoria permeated the utopian imagery of Samuel Butler. His pioneering years as a settler are vividly rendered in A First Year in the Canterbury Settlement (1863) and in the journal Samuel Butler at Mesopotamia (first published 1960). In Erewhon (1872) New Zealand is re-figured as an ambiguous utopian otherwhere, taking shape through assimilation and displacement, both geographical and conceptual. New Zealand was powerfully mythicised in the nineteenth century and its myth of foundation has been constantly reinforced. Butler’s renditions of the British colony and its settlers are pivotal in understanding the de/construction of New Zealand’s identity in the contemporary age, in which bipolar attitudes towards national identities have been exacerbated.